DEVELOPMENT AND EVALUATION OF THE ANTICANCER, ANTIOXIDANT, AND ANTIMICROBIAL ACTIVITIES OF CYPRESS OIL NANOEMULGEL - Shahin, Aya (An-Najah National University, 2024)
Background: Cypress oil is a potent essential oil known for its wide range of therapeutic activities. Objectives: This study aimed to incorporate cypress oil into nanoemulgels to overcome their low solubility and high volatility. Methodology: Gas chromatography-mass spectrometry identified the chemical composition. The cypress oil nanoemulsion was optimized, and then it was incorporated with Carbopol hydrogel to produce cypress oil nanoemulgel. DPPH scavenger technique measured the cypress oil and its nanoemulgel antioxidant activity. Then, the droplet size, PDI, zeta potential, rheology, antimicrobial, anticancer, and anti-inflammatory activities were evaluated utilizing reference methods. Results: The chemical composition of cypress oil is predominantly composed of monoterpene hydrocarbons, with α-pinene as the major component (50.72%), followed by 3-b-carene (27.57%). The ternary phase diagram revealed that the nanoemulsion containing 40% Tween, 10% Span, and 50% cypress oil had an optimized droplet size of 105.28 ±2.12 nm and a PDI of 0.112 ±0.016 nm. The cypress nanoemulgel formulation showed no significant change in droplet size or PDI, while it has a zeta potential of -33 mV. Moreover, the antioxidant efficiency of cypress oil was IC50 = 14.7 ±0.3 μg/mL, while it was reduced to more than half for nanoemulgel with IC50=6.6 ±0.13 µg/ml. Potent antibacterial activity was reported against several gram-positive and gram-negative bacteria, with inhibition zones in the 11–36 mm range. Also, effective antifungal activity was noticed against different species of Candida albicans in the range of 16–24 mm. The formulated nanoemulgel had better activity compared to the oil alone. Furthermore, it was more potent than the oil as an anticancer agent against Hep-G2 cells, with an IC50 of 39.81 µg/ml, followed by 58.88 and 61.65 µg/ml for MCF-7 and HeLa cell line. It also demonstrated an anti-fibrotic effect with an IC50 of 63.09 µg/ml against LX-2 cell line. The cypress oil nanoemulgel was more selective for COX-2 than COX-1. In addition, the IC50 of the nanoemulgel toward COX-2 (13.96 µg/ml) was almost half the value for the oil (28.78 µg/ml). Conclusion: The overall findings suggest that cypress oil nanoemulgel holds promise to counteract several skin infections and cancer cell lines. However, further in vivo studies are needed.
تطوير وتقييم الأنشطة المضادة للسرطان ومضادات الأكسدة ومضادات الميكروبات لمستحضر النانو ايملجل لزيت السرو